2018
DOI: 10.3390/sym10090394
|View full text |Cite
|
Sign up to set email alerts
|

Products and Mechanistic Investigations on the Reactions of Hydrazines with Ozone in Gas-Phase

Abstract: The toxic transformation products of hydrazines are of great concern. These products’ properties combined with their formation mechanisms are needed to assess their potential environmental and human impacts. In this study, the gas-phase reaction of hydrazine (N2H4), monomethyldrazine (MMH) and unsymmetrical dimethyhydrazine (UDMH) with O3 have been studied at varying reactant ratios, both in the presence and absence of a radical trap. Gas chromatography-mass spectroscopy (GC-MS) has been implied to follow reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In order to reduce excessive NDMA formation, identifying potential NDMA precursors and their reactivity are crucial [ 39 , 40 ]. Organic hydrazine compounds such as unsymmetrical hydrazine (UDMH) and monomethylhydrazines (MMH), being the major NDMA precursors, upon ozonation form NDMA up to 90% in molar yields [ 41 ]. They act as eco-toxicants and can form several toxic transformation products, posing severe health risks [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce excessive NDMA formation, identifying potential NDMA precursors and their reactivity are crucial [ 39 , 40 ]. Organic hydrazine compounds such as unsymmetrical hydrazine (UDMH) and monomethylhydrazines (MMH), being the major NDMA precursors, upon ozonation form NDMA up to 90% in molar yields [ 41 ]. They act as eco-toxicants and can form several toxic transformation products, posing severe health risks [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since these hydrazines do not undergo photolysis in the solar actinic region (>290nm), UDMH and MMH are more likely to react with ozone in the atmosphere to form NDMA along with other toxicants. Huang et al [ 41 ] found that the conversion rate of UDMH and MMH to NDMA on ozonation depends on the O 3 /MMH or UDMH ratios. With excess ozone, UDMH and MMH produce 88% and 58% of NDMA, respectively, in molar yields, making them the foremost ozone-NDMA precursors.…”
Section: Introductionmentioning
confidence: 99%